GENERAL INFORMATION ABOUT WATER INTAKE FACILITIES . CONDITIONS AND CLASSIFICATION OF WATER INTAKE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article provides information on water intake structures used in the water management sector and information on water intake structures currently used in water management. The location of water intake structures is discussed in detail.